Improving Relative Bioavailability of Oral Imidazolidinedione by Reducing Particle Size Using Homogenization and Ultra-Sonication. (21st March 2019) - Zeng, Qiang; Xie, Lisa; Zhang, Jing; Vuong, Chau; Potter, Brittney; Aylor, Samantha; Sousa, Jason; Black, Chad; Li, Qigui
Abstract: Particle size is an important determinant of gastrointestinal absorption of compounds administrated orally. The present study evaluates the effect of a reduction in particle size assessed by homogenization, sonication, and homogenization plus sonication on the bioavailability of imidazolidinedione (IZ), an antimalarial compound with known causal prophylactic activity and radical cure of relapsing malaria. Formulations were administrated intragastrically to mice, and blood samples were collected for LC-MS/MS analysis. The homogenization method manually decreased particle size with minimal variance, resulting in a mean particle diameter of 42.22 μm, whereas the probe sonication method evenly distributed pulses of sound to break apart particles, resulting in a mean diameter of 1.50 μm. Homogenization plus sonication resulted in a mean particle diameter of 1.44 μm, which was similar to that of the sonication method alone. The compound suspensions did not show a significant difference in mean particle size between the different vehicles. The sonically engineered microparticle delivers high sonic energy to the suspension leads to faster breakdown and stabilizing of the micronized particles when compared with homogenizer. The bioavailability of the small particle IZ formulation was 100%, compared to the 55.79% relative bioavailability of IZ with larger particle size. These initial data clearly show that a reduction in particle size of orally administered IZ with probe sonication could significantly increase bioavailability in rodent animals that is affected by a high first-pass effect.